Measurement of forward W and Z boson production in association with jets in proton-proton collisions at √s = 8 TeV - Aaij, Roel; Abellán Beteta, C.; Adeva, B.; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; et al. (Journal of high energy physics, 2016)
The production of W and Z bosons in association with jets is studied in the forward region of proton-proton collisions collected at a centre-of-mass energy of 8 TeV by the LHCb experiment, corresponding to an integrated luminosity of 1.98 ± 0.02 fb−1. The W boson is identified using its decay to a muon and a neutrino, while the Z boson is identified through its decay to a muon pair. Total cross-sections are measured and combined into charge ratios, asymmetries, and ratios of W +jet and Z+jet production cross-sections. Differential measurements are also performed as a function of both boson and jet kinematic variables. All results are in agreement with Standard Model predictions.